The Effect of Quadriceps Strength and Proprioception on Risk for Knee Osteoarthritis - Segal, Neil A. (2010)
PURPOSE: Impaired quadriceps strength and joint position sense (JPS) have been linked with knee osteoarthritis (OA) cross-sectionally. While neither has been independently associated with incident radiographic OA, their combination may mediate risk. The purpose of this study was to determine whether better sensoriomotor function protects against development of incident radiographic or symptomatic knee OA. METHODS: The Multicenter Osteoarthritis (MOST) Study, is a longitudinal study of adults age 50-79 years at high risk for knee OA. Participants underwent bilateral, weight bearing, fixed-flexion radiographs, JPS acuity tests, and isokinetic quadriceps strength tests. The relationships between combinations of the tertiles of sex-specific baseline peak strength and mean JPS, and development of incident radiographic (Kellgren-Lawrence (KL) grade ≥2) or symptomatic knee OA (KL grade ≥2 and frequent knee pain or stiffness) at 30-month follow-up were evaluated. Secondary analyses defined JPS as the variance over the 10 JPS trials, and also assessed the interaction of strength and JPS in predicting each outcome. RESULTS: The study of incident radiographic knee OA included 1390 participants (age 61.2±7.9 years and BMI 29.4±5.1 kg/m(2)) and the study of incident symptomatic knee OA included 1829 participants (age 62.2±8.0 years and BMI 30.0±5.4 kg/m(2)). Greater strength at baseline protected against incident symptomatic but not radiographic knee OA regardless of JPS tertile. There was no significant relationship between the strength–JPS interaction and the development of radiographic or symptomatic knee OA. CONCLUSION: The finding that quadriceps strength protected against incident symptomatic but not radiographic knee OA regardless of JPS tertile suggests that strength may be more important than JPS in mediating risk for knee OA.